Software de vendas e divulgação de eventos para a casa noturna Tianena - CIANCAGLIO, Gabriel Bauer; LIMA, Fábio Lucas Martins Da Silva; PORTA, Renan Andreata; LUCAS, Wellington Fernandes (163, 2020)
O sistema de informação revolucionou a maneira de fazer propagandas, vendas e administrar negócios. Com isso é indispensável o uso de um sistema próprio para empresas que querem ter competitividade no atual mercado. Com a proposta de auxiliar na divulgação e administração de vendas de ingressos, o objetivo geral desse trabalho é desenvolver e implementar uma aplicação mobile capaz de atender a empresa Tianena Music Bar, do segmento de eventos noturnos, de modo que a vendas e divulgações se tornem simples e eficazes. Pretende-se que todas informações referentes a clientes, funcionários e administradores, sejam armazenadas e administradas através da aplicação. Conclui-se que os sistemas são fundamentais para o sucesso de um negócio e de grande aprendizado para formandos de um curso de análise e desenvolvimento de sistemas. Espera-se com esse tipo de trabalho que a empresa consiga organizar a informações, otimizar vendas e melhorar a divulgação de seus eventos.

The information system has revolutionized the way of advertising, selling and running businesses. As a result, it is essential to use a proper system for companies that want to be competitive in the current market. With the proposal to assist in the dissemination and administration of ticket sales, the general objective of this work is to develop and implement a mobile application capable of serving the company Tianena Music Bar, in the segment of night events, so that sales and disclosures become simple and effective. It is intended that all information regarding customers, employees and administrators, be stored and managed through the application. It is concluded that the systems are fundamental for the success of a business and of great learning for graduates of a course of analysis and development of systems. With this type of work, it is expected that the company will be able to organize information, optimize sales and improve the dissemination of its events. The systems are fundamental for the success of a business and of great learning for graduates of an analysis and development course. systems. It is expected with this type of work that the company will be able to organize information, optimize sales and improve the dissemination of its events.
Keywords: Desenvolvimento de software (eventos); Empresas organizadoras de eventos; Informação e Comunicação